Study of thermodynamic interaction parameters of poly(p-naphthalene-2(?) sulfonyl styrene) using inverse gas chromatography - Kaya, I; Demirelli, K (Freund Publishing House Ltd, 1999)
We used the inverse gas chromatographic technique to find some thermodynamic parameters, such as average partial molar enthalpy, Delta H-1(infinity) partial molar free energy, Delta G(1)(infinity), weight fraction activity coefficient, Delta Omega(1)(infinity) and the Flory-Huggins interaction parameter, chi(12)(infinity), for poly(p-naphthalene-2(beta) sulfonyl styrene) organic solvents systems at infinite dilution. The values of chi(12)(infinity) found in this experiment were high for alkanes, o-xylene, and toluene, as is usual for polymer-nonsolvent systems, but were lower for alcohols, acetates, ketones, and benzene, as is usual for poly(p-naphthalene2(beta) sulfonyl styrene) solvents systems. Similar results were obtained for Delta Omega(1)(infinity) in the same system. Additionally, the solubility parameter of poly(p-naphthalene-2(beta) sulfonyl styrene), were calculated as 6.75 (cal/cm(3))(0.5) and 6.81 (cal/cm(3))(0.5) from the slope or intercept of [(delta(1)(2)/RT)-chi(12)(infinity)/V-1]= (2 delta(2)/RT)delta(1) - delta(2)(2) / RT, at 180 degrees C, respectively.
Keywords: polymer-solvent thermodynamic interactions; igc technique